Skin and Soft Tissue Lesions in a District Hospital in Central Nigeria: A Histopathological Study - Babatunde M. Duduyemi; Abidemi E. Omonisi; Nicholas A. Titiloye (Dermatology Research and Practice)
Introduction. Skin and soft tissue diseases form a large and heterogeneous group of mesenchymal extraskeletal and dermatologic lesions in humans. Diseases of the skin and soft tissue can develop virtually anywhere in the body, extremities, the trunk, the retroperitoneum, the head, and the neck. Our study aims to review skin and soft tissue specimens from our centre describing the histopathological patterns. Method. A cross sectional study was done using secondary data of all skin and soft tissue specimens over a 3 year period. Patients’ demographics, sites of specimen, and histological diagnoses were extracted from the surgical day book. The data were analysed in terms of age and sex distribution and histological characteristics of pathologic lesions using the SPSS version 22. The data for these patients were presented in tables and figures. Result. 451 skin and soft tissue specimens constituting 18% of all the specimens with an M : F ratio of 1 : 1.2. The age range of our patients was 4–85 years with a mean of 33.52 ± 15.05 years. The peak age of occurrence was 30–39 years. Most of our cases were seen in the extremities (50.7%) followed by head (22.2%), while the least common sites were the perineal and neck areas (5.3% each). The commonest site in females was the upper limb (32.4%); the head and lower limb were the commonest sites in males (28.4% each). Most of our patients have neoplastic lesions of skin and soft tissue constituting 68.3%, inflammatory lesions (16.9%), and the least common lesion being hamartoma (0.2%). The most common category of lesions includes inflammatory (nonspecific dermatitis 6.5%); cysts (dermoid cyst 6%); reactive (hypertrophic scar 1%); and neoplastic (lipoma 32.4%). The benign neoplasms were more common (92.9%) than the malignant ones (7.1%). The neoplastic lesions were relatively more common in males than females and the reverse was true for the inflammatory lesions. Conclusion. Skin and soft tissue lesions are relatively common in our environment with majority being benign neoplastic lesion.